Constructed Wetlands for Treatment of Acid Mine Drainage: A Review - Yudha Gusti Wibowo; Candra Wijaya; Petrus Halomoan; Aryo Yudhoyono; Muhammad Safri (Universitas Diponegoro, 2022)
The coal mining industry is an industrial activity that impacts the environment. This activity will generate acid mine drainage due to the interaction of water, air and sulfide minerals. Acid mine drainage is wastewater with low pH and heavy metals content. These conditions will be given some negatives impact on the environment and human health. The low-cost, applicable and simple method to solve acid mine drainage in mining areas is constructed wetlands. Hence, this paper aims to describe the potential of wetlands as a low-cost and applicable method for acid mine drainage treatment. This paper also describes the holistic information about an overview of constructed wetlands, acid mine drainage (AMD) production and their negative impacts, recent trends in constructed wetlands, recommendation components of wetlands, potential application in rural areas and future considerations